Three-dimensional characteristics of nystagmus induced by low frequency in semicircular canals of healthy young people - Huang, Xiaobang; Zhang, Xueqing; Deng, Qiaomei; Li, Shanshan; Liu, Qiang; Wen, Chao; Wang, Wei; Chen, Taisheng (Frontiers in Neuroscience, 2024)
The study aimed to analyze the three-dimensional characteristics of nystagmus induced by different semicircular canal combinations in healthy young people, and to determine the reference range of nystagmus slow phase velocity (SPV) and its asymmetry.Fifty-two healthy volunteers (26 males and 26 females, aged 17-42 years, average 23.52 ± 6.59), were recruited to perform the manual triaxial rotation testing with a 3D-Videonystagmography (3D-VNG) device (VertiGoggles (ZT-VNG-II), Shanghai ZEHNIT Medical Technology Co., Ltd., Shanghai, China) using a 0.3 Hz prompt beat and a 90° amplitude, respectively. The induced nystagmus around the Z-, X-, and Y-axes were recorded in the yaw, pitch, and roll planes. The directions and slow phase velocities of the horizontal, vertical, and torsional components of the induced nystagmus under different semicircular canal combinations (the left lateral and right lateral semicircular canal combination, bilateral anterior semicircular canals, bilateral posterior semicircular canals combination, and the anterior and posterior semicircular canals 删除了: ,